Configuração de osciloscópio e aquisição de dados via Matlab - Isabele Cristine do, Nascimento (2022)
The oscilloscope is one of the most used equipaments on the university laboratories for voltage signal wave form visualization and data acquisition and processing, being fundamental in classes such as electric circuits eletronics, electronic instrumentation, among others. The present paper has the goal of execute the communication between the equipment and MatLab, in order to control it9s settings through the software, such as collect the data so that it can be visualized, stored and the use of data with others signal processing routines of the software. So that the experience become more ritch regarding time optimization and spent efforts, once that a large amount of students presentes difficulties handling the device, such as the difficulties to analyse the data aquiried from the oscilloscope, given that this one is limited regarding data storage. Therefore, three functions had been created throught the connection between oscilloscope and MatLab, meaning to: send settings commands; receiving current settings information and get in acessible formats the data acquiried through the equipment on MatLab.